Psychosocial effects of whole-body MRI screening in adult high-risk pathogenic TP53 mutation carriers: a case-controlled study (SIGNIFY). Issue 4 (12th November 2019) - Bancroft, Elizabeth K; Saya, Sibel; Brown, Emma; Thomas, Sarah; Taylor, Natalie; Rothwell, Jeanette; Pope, Jennifer; Chamberlain, Anthony; Page, Elizabeth; Benafif, Sarah; Hanson, Helen; Dias, Alexander; et al.
Abstract : Background: Germline TP53 gene pathogenic variants (pv) cause a very high lifetime risk of developing cancer, almost 100% for women and 75% for men. In the UK, annual MRI breast screening is recommended for female TP53 pv carriers. The SIGNIFY study (Magnetic Resonance Imaging screening in Li Fraumeni syndrome: An exploratory whole body MRI) study reported outcomes of whole-body MRI (WB-MRI) in a cohort of 44 TP53 pv carriers and 44 matched population controls. The results supported the use of a baseline WB-MRI screen in all adult TP53 pv carriers. Here we report the acceptability of WB-MRI screening and effects on psychosocial functioning and health-related quality of life in the short and medium terms. Methods: Psychosocial and other assessments were carried out at study enrolment, immediately before MRI, before and after MRI results, and at 12, 26 and 52 weeks' follow-up. Results: WB-MRI was found to be acceptable with high levels of satisfaction and low levels of psychological morbidity throughout. Although their mean levels of cancer worry were not high, carriers had significantly more cancer worry at most time-points than controls. They also reported significantly more clinically significant intrusive and avoidant thoughts about cancer than controls at all time-points. There were no clinically significant adverse psychosocial outcomes in either carriers with a history of cancer or in those requiring further investigations. Conclusion: WB-MRI screening can be implemented in TP53 pv carriers without adverse psychosocial outcomes in the short and medium terms. A previous cancer diagnosis may predict a better psychosocial outcome. Some carriers seriously underestimate their risk of cancer. Carriers of pv should have access to a clinician to help them develop adaptive strategies to cope with cancer-related concerns and respond to clinically significant depression and/or anxiety.